Cytotoxic activity of leaf and rhizome extracts of Alpinia scabra (Blume) Naves, a wild ginger from peninsular Malaysia - Ibrahim, H.; Sim, K.S.; Syamsir, D.R.; Nor, N.R.M.; Nurestri, A.M.S.; Awang, K. (Academic Journals, 2010)
The leaves and rhizomes of Alpinia scabra (Zingiberaceae) were investigated for their cytotoxic effect against selected human cancer cell lines, namely MCF7 (hormone-dependant breast carcinoma cell line), HT29 (colon carcinoma cell line) and SKOV-3 (ovarian cancer cell line) by using an in vitro neutral red cytotoxicity assay. The methanol extracts of both leaves and rhizomes did not show active cytotoxic activity against the selected cancer cell lines. The n-hexane extract of the leaves exhibited remarkable cytotoxic effect against SKOV-3 cells with IC(50) value of 6.3 mu g/ml while dichloromethane extract showed high cytotoxic effect against MCF7 and SKOV-3 with IC(50) values of 6.7 and 5.9 mu g/ml, respectively. The n-hexane and dichloromethane extracts of the rhizomes possessed high cytotoxic effect against SKOV-3 cells with IC(50) values of 8.3 and 7.0 mu g/ml, respectively. This is the first report of the cytotoxic activity of A. scabra.